Empowering students: positive higher education strategies - Li, Honghuan (Frontiers in Psychology, 2025)
Student wellbeing in higher education has been increasingly recognized as a necessary companion to academic achievement. This narrative review examines positive education interventions through the frameworks of Self-Determination Theory (SDT), the PERMA framework, the PROSPER framework, and the Study Demands–Resources (SD-R) Theory, which highlight the importance of autonomy, competence, relatedness and holistic wellbeing in promoting engagement, resilience and intrinsic motivation. The research discusses practical strategies such as mindfulness, strengths-based learning, and growth mindset cultivation and their alignment with institutional policies and emerging technologies for personalized learning. It also identifies challenges such as scalability, cultural adaptation and equity by providing actionable recommendations for building supportive, wellbeing-centered learning environments.